Electroactive material for metal-ion battery
Patent Information
- Application Number
- JP2024202067
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-09
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2039-11-08
Smart Images

Figure 2025026956000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates generally to electroactive materials suitable for use in electrodes for rechargeable metal-ion batteries, and more particularly to particulate materials having high mechanical strength with high electrochemical capacity suitable for use as anode active materials in rechargeable metal-ion batteries. [Background technology]
[0002] Rechargeable metal-ion batteries are widely used in portable electronic devices such as mobile phones and laptops, and are increasingly being applied in electric or hybrid vehicles. Rechargeable metal-ion batteries generally include an anode layer, a cathode layer, an electrolyte that transports metal ions between the anode and cathode layers, and an electrically insulating porous separator disposed between the anode and cathode. The cathode typically includes a metal current collector with a layer of metal ion containing metal oxide-based composite material, and the anode typically includes a metal current collector with a layer of electroactive material, defined herein as a material capable of inserting and releasing metal ions during charging and discharging the battery. For the avoidance of doubt, the terms "cathode" and "anode" are used herein in the sense that the battery is loaded such that the cathode is the positive electrode and the anode is the negative electrode. When the metal-ion battery is charged, metal ions are transported from the metal ion-containing cathode layer through the electrolyte to the anode and inserted into the anode material. The term "battery" is used herein to refer to both devices containing a single anode and a single cathode, and devices containing multiple anodes and / or multiple cathodes.
[0003] There is interest in improving the gravimetric and / or volumetric capacity of rechargeable metal-ion batteries. The use of lithium-ion batteries has already provided significant improvements over other battery technologies, but there is room for further development. To date, commercially available lithium-ion batteries have been primarily limited to the use of graphite as the anode active material. Upon charging a graphite anode, lithium is inserted between the graphite layers, resulting in a charge-discharge reaction with the empirical formula Lix C6, where x is greater than 0 and less than or equal to 1. As a result, graphite has a maximum theoretical capacity of 372 mAh / g in lithium-ion batteries, with practical capacities somewhat lower (approximately 340 mAh / g to 360 mAh / g). Other materials, such as silicon, tin, and germanium, can intercalate lithium at significantly higher capacities than graphite, but are not yet in widespread commercial use due to the difficulty of maintaining sufficient capacity over many charge-discharge cycles.
[0004] In particular, silicon has been recognized as a promising alternative to graphite in the manufacture of rechargeable metal-ion batteries with high gravimetric and volumetric capacities due to its extremely high capacity relative to lithium (see, for example, Non-Patent Document 1). Silicon has a theoretical maximum specific capacity of about 3600 mAh / g (Li ion battery) at room temperature. 15 However, the use of silicon as an anode material is complicated by its large volume change upon charging and discharging.
[0005] When lithium is intercalated into bulk silicon, the volume of the silicon material increases significantly, up to 400% of its original volume when the silicon is lithiated to its maximum capacity. Then, repeated charge-discharge cycles generate significant mechanical stresses in the silicon material, leading to fracture and delamination of the silicon anode material. The volumetric shrinkage of silicon particles upon delithiation can result in loss of electrical contact between the anode material and the current collector. To make matters even more difficult, the solid electrolyte interface (SEI) layer formed on the silicon surface is not mechanically durable enough to accommodate the expansion and contraction of silicon. As a result, the newly exposed silicon surface causes further decomposition of the electrolyte, an increase in the thickness of the SEI layer, and Lithium will be irreversibly consumed. Collectively, these failure mechanisms result in an unacceptable loss of electrochemical capacity over successive charge-discharge cycles.
[0006] Numerous approaches have been proposed to overcome the problems associated with the volume changes observed during charging of silicon-containing anodes. The most prevalent approach to address irreversible capacity loss in silicon-containing anodes is the use of some form of microstructured silicon as the electroactive material. It has been reported that fine silicon structures with cross sections less than about 150 nm, such as silicon films and silicon nanoparticles, are more resistant to volume changes during charging and discharging compared to silicon particles in the micron size range. However, none of these are particularly suitable for commercial scale application without morphology modification. Nanoscale particles are difficult to manufacture and handle, and silicon films do not provide sufficient bulk capacitance. For example, nanoscale particles tend to form agglomerates, which makes it difficult to effectively disperse the particles within the anode material matrix. The formation of nanoscale particle agglomerates also results in unacceptable capacity loss during repeated charge-discharge cycles.
[0007] Ohara et al. (Non-Patent Document 2) evaporated silicon as a thin film onto a nickel foil current collector. and the use of this structure as an anode in a lithium-ion battery. Although this approach provides good capacity retention, the thin film structure does not provide a useful amount of capacity per unit area, and any improvement is eliminated as the film thickness increases.
[0008] US Pat. No. 5,399,433 discloses that capacity retention can be improved by using silicon particles with a high aspect ratio, ie, the ratio of the maximum dimension to the minimum dimension of the particle.
[0009] It is also generally known that electroactive materials such as silicon can be deposited within the pores of porous support materials such as activated carbon materials. These composite materials offer some of the beneficial charge-discharge properties of nanoscale silicon particles while avoiding the difficulties of handling nanoparticles. For example, Guo et al. (Non-Patent Document 3) reported that porous carbon substrates are deposited with silicon particles uniformly distributed within the substrate's pore structure. discloses a silicon-carbon composite that provides a conductive scaffold with silicon nanoparticles stacked on top of each other. The formation of the SEI during the first charge cycle is confined to the remaining pore volume such that the remaining silicon is not exposed to the electrolyte during subsequent charge cycles. The composite shows improved capacity retention over multiple charge cycles, but the initial capacity in mAh / g of the composite is significantly lower than that for silicon nanoparticles.
[0010] US Patent No. 5,999,336 discloses an active material comprising a carbon-based scaffold having small pores branching off from a small number of larger pores. An electroactive material (e.g., silicon) is randomly located on the walls of both the large and small pores, as well as on the outer surface of the carbon-based scaffold.
[0011] Despite previous efforts, there is a continuing need for improvements in the electrochemical storage capacity of lithium-ion batteries. In particular, composite materials that rely on porous support materials with electroactive materials deposited in their pore structure often have insufficient structural strength for commercial use. Conventional electrode fabrication processes typically rely on calendaring of electrode materials onto current collectors to densify the electrode layers and optimize space utilization within the battery design. Highly porous materials are prone to breakage during electrode fabrication, leading to reduced electrochemical performance. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] International Publication No. 2007 / 083155 [Patent Document 2] JP 2003-100284 A [Non-patent literature]
[0013] [Non-Patent Document 1] Insertion Electrode Materials for Rechargeable Lithium Batteries, Winter, M. et al. in Adv. Mater. 1998, 10, No. 10 [Non-Patent Document 2] Journal of Power Sources 136 (2004) 303-306 [Non-Patent Document 3] Journal of Materials Chemistry A, 2013, pp. 14075-14079 Summary of the Invention [Problem to be solved by the invention]
[0014] The present invention is based on the discovery that the mechanical performance of composite particles comprising a porous carbon skeleton and an electroactive material located within the porous carbon skeleton can be optimized by using a porous carbon skeleton with a specific pore structure and at the same time a carefully controlled pore size distribution. [Means for solving the problem]
[0015] In a first aspect, the present invention provides a particulate material comprising a plurality of composite particles, the composite particles comprising: (a) a porous carbon framework containing micropores and / or mesopores, The micropores and mesopores have a total pore volume of P measured by gas adsorption. 1 cm 3 / g, where P 1 has a value of at least 0.6, PD measured by gas adsorption 50 a porous carbon skeleton having pores with a diameter of 2 nm or less; (b) an electroactive material located within the micropores and / or mesopores of the porous carbon framework; and Including, The composite particles have a diameter of 10 μm or less. 90 A particulate material is provided having a particle size.
[0016] The present invention thus relates to a particulate material in which the porous carbon skeleton has a relatively high total volume of micropores and mesopores, with pores having a diameter of 2 nm or less constituting at least 50% of the total pore volume, and with a particle size distribution heavily skewed towards particles having a diameter of 10 μm or less. For the avoidance of doubt, references herein to the pore volume of a porous carbon skeleton (unless expressly stated to the contrary) relate to the pore volume of the porous carbon skeleton when measured alone, i.e. in the absence of any electroactive material (or other material) occupying the pores of the porous carbon skeleton.
[0017] It has been found that the combination of small particle size and highly divided pore volume provides an electroactive material that is highly resistant to mechanical degradation during electrode fabrication. The highly fine pore structure of the porous carbon skeleton results in very fine pore walls. Without being bound by theory, it is believed that these very fine pore walls can be elastically deformed with low fracture rates, making the skeleton very resistant to fracture under compressive stress. Control of the pore size distribution not only additionally contributes to particle strength, but also allows for improved close packing of the composite particles in the electrode active layer, thereby reducing the need for excessive calendering pressure.
[0018] A further advantage of the particulate material of the present invention is that the highly microporous carbon skeleton has a high tensile fracture strength, so that it can accommodate within its pore volume at least a portion of the expansion of the electroactive material without breaking. Once the electroactive material is fully lithiated, the composite particle as a whole may expand somewhat externally, but the amount of external expansion is limited by the internally accommodating expansion. Until the material expands outward, the highly microporous carbon skeleton can deform without breaking. The high total porosity of the porous carbon skeleton not only provides a high volumetric loading of the electroactive material, but also ensures that the porous carbon skeleton is sufficiently resilient to withstand repeated volume changes over multiple charge-discharge cycles.
[0019] The highly microporous carbon framework offers the added advantage that the electroactive material is located within the micropore network in the form of small domains with dimensions on the order of a few nanometers or less. These fine electroactive structures are less resistant to elastic deformation and more resistant to fracture than larger electroactive structures, allowing them to be lithiated and delithiated without excessive structural stress. Thus, the highly microporous nature of the porous carbon framework not only provides improved mechanical strength of the particles, but also ensures that the electroactive material is sufficiently elastic to withstand repeated volume changes over multiple charge-discharge cycles without significant capacity loss.
[0020] Yet another factor in the exceptional performance of the particulate materials of the present invention is that the formation of SEI is minimized. As discussed above, the electroactive material is located within small mesopores and / or micropores, limiting the formation of SEI since only a small area of the electroactive material surface is accessible to the electrolyte. Additional exposure of the electroactive material upon subsequent charge / discharge cycles is substantially prevented such that the formation of SEI is not a significant failure mechanism that can lead to capacity loss. This is the case, for example, with the materials disclosed by Guo. This is in clear contrast to the characteristic excessive and unconstrained formation of SEI (see above).
[0021] The porous carbon framework preferably comprises a three-dimensionally interconnected open pore network comprising a combination of micropores and / or mesopores, and optionally a small amount of macropores. In accordance with conventional IUPAC terminology, the term "micropores" is used herein to refer to pores with a diameter of less than 2 nm, the term "mesopores" is used herein to refer to pores with a diameter of 2 nm to 50 nm, and the term "macropores" is used herein to refer to pores with a diameter of more than 50 nm.
[0022] References herein to the volume of micropores, mesopores, and macropores within a porous carbon skeleton, as well as any reference to the pore volume distribution within a porous carbon skeleton, refer to the internal pore volume of the porous carbon skeleton alone (i.e., in the absence of electroactive material or other materials occupying some or all of the pore volume).
[0023] The porous carbon framework is characterized by a high pore volume in the form of micropores and / or mesopores. As used herein, the total volume of micropores and mesopores (i.e., the total pore volume in the range of 0 nm to 50 nm) is defined as P 1 cm 3 / g, where P 1 represents a dimensionless natural number having a value of at least 0.6. More preferably, P 1 is at least 0.65, or at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85. 1 may be at least 0.9, or at least 0.95, or at least 1, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.2.
[0024] The use of a highly porosity carbon skeleton is advantageous as it allows a greater amount of electroactive material to be accommodated within the pore structure, while the division of the pore volume into fine mesopores and micropores ensures that the composite particles have sufficient resistance to the compressive stresses used in conventional electrode manufacturing processes.
[0025] The internal pore volume of the porous carbon skeleton is preferably limited at a value where the increased fragility of the porous carbon skeleton outweighs the benefit of increased pore volume to accommodate a larger amount of electroactive material. 1 The value of P may be less than or equal to 2.5. However, more preferably, 1 The value of P may be 2.4 or less, or 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less. More preferably, P1 The value of is 1.2 or more. or 1.1 or less, or 1.0 or less, or 0.9 or less.
[0026] According to the present invention, P 1 The value of is, for example, in the range of 0.8 to 2.2, or in the range of 0.85 to 2.2, or in the range of 0.9 to 2.2, or in the range of 0.95 to 2.2, or in the range of 1 to 2.2, or in the range of 1.05 to 2.2, or in the range of 1.1 to 2.2, or in the range of 0.8 to 2, or in the range of 0.85 to 2, or in the range of 0.9 to 2, or in the range of 0.95 to 2, or in the range of 1 to 2, or in the range of 1.05 to 2, or in the range of 1.1 to 2, or in the range of 0.8 to 1.9, or in the range of 0.85 to 1.9, or in the range of 0.9 to 1.9, or in the range of 0.95 to 1.9, or in the range of 1 to 1.9, or in the range of 1.05 to 1.9, or in the range of 1.1 to 1.9, or in the range of 0.8 to 1. The range of 0.8, or 0.85 to 1.8, or 0.9 to 1.8, or 0.95 to 1.8, or 1 to 1.8, or 1.05 to 1.8, or 1.1 to 1.8, or 0.8 to 1.7, or 0.85 to 1.7, or 0.9 to 1.7, or 0.95 to 1.7, or 1 to 1.7, or 1.05 to 1.7, or 1.1 to 1.7, or 0.8 to 1.6, or 0.85 to 1.6, or 0.9 to 1.6, or 0.95 to 1.6, or 1 to 1.6, or 1.05 to 1.6, or 1.1 to 1.6.
[0027] Preferably, P 1 The value can be, for example, in the range of 0.6 to 1.4, or in the range of 0.65 to 1.4, or in the range of 0.7 to 1.4, or in the range of 0.75 to 1.4, or in the range of 0.7 to 1.3, or in the range of 0.75 to 1.3, or in the range of 0.7 to 1.2, or in the range of 0.75 to 1.2, or in the range of 0.7 to 1, or in the range of 0.75 to 1, or in the range of 0.7 to 0.9, or in the range of 0.75 to 0.9.
[0028] PD of porous carbon frameworks 50 The pore size is 2 nm or less.50 The term "pore size" refers to the median pore size on a volumetric basis based on the total volume of micropores and mesopores (i.e., the pore size less than or equal to the P 1 (the pore size at which 50% of the total micropore and mesopore volume is present, represented by 1.0 mm). Thus, according to the invention, at least 50% of the total volume of the micropores and mesopores has the form of pores with a diameter of 2 nm or less.
[0029] As used herein, "PD n The general term "pore size" refers to the nth percentile pore size on a volume basis based on the total volume of micropores and mesopores. For example, "D 90 The term "pore size" refers to the size of the pores that are smaller than the P 1 (Refers to the pore size at which 90% of the total micropore and mesopore volume is present, represented by
[0030] For the avoidance of doubt, any macropore volume (pore diameters greater than 50 nm) is not included in the PD n It is not taken into account for the purpose of calculating the value.
[0031] According to the present invention, PD of the porous carbon skeleton 50 The pore size is preferably 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less, or 1.2 nm or less, or 1 nm or less. 80 The pore size is at least 0.8 nm, or at least 1 nm, or at least 1.2 nm.
[0032] More preferably, at least 60% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 3 nm or less. 60 The pore size is preferably 3 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less, or 1.2 nm or less.
[0033] More preferably, at least 70% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 3.5 nm or less. 70 The pore size is preferably 3.5 nm or less, or 3 nm or less, or 2.5 nm or less, or 2.2 nm or less, or 2 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less.
[0034] More preferably, at least 80% of the total micropore and mesopore volume of the porous carbon skeleton has a pore morphology with a diameter of 5 nm or less. 80 The pore size is preferably 5 nm or less, or 4.5 nm or less, or 4 nm or less, or 3.5 nm or less, or 3 nm or less, or 2.5 nm or less, or 2.2 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less.
[0035] The larger mesopore volume in the porous carbon framework is preferably PD 90 The pore size is restricted to be 10 nm or less, or 8 nm or less, or 6 nm or less, or 5 nm or less, or 4 nm or less, or 3 nm or less, or 2.5 nm or less, or 2 nm or less.
[0036] Preferably, PD 95 The pore size is 15 nm or less, or 12 nm or less, or 10 nm or less.
[0037] According to the invention, the porous carbon skeleton is 50 is 2 nm or less, and PD 90 is 10 nm or less, or PD 50 is 2 nm or less, and PD 90 is 8 nm or less, or PD 50 is 2 nm or less, and PD 90 is 6 nm or less, or PD 50 is 1.8 nm or less, and PD 90 is 8 nm or less, or PD 50is 1.8 nm or less, and PD 90 is 6 nm or less, or PD 50 is 1.6 nm or less, and PD 90 is 6 nm or less, or PD 50 is 1.2 nm or less, and PD 90 is 5 nm or less, or PD 50 is 1 nm or less, and PD 90 is 4 nm or less, or PD 50 is 1 nm or less, and PD 90 is 3 nm or less, or PD 50 is 1 nm or less, and PD 90 is 2.5 nm or less, or PD 50 is 1 nm or less, and PD 90 may be 2 nm or less.
[0038] More preferably, the porous carbon skeleton is PD 50 is 1 nm to 2 nm, and PD 90 is 3nm to 10nm, or PD 50 is 1 nm to 2 nm, and PD 90 is 3nm to 8nm, or PD 50 is 1 nm to 2 nm, and PD 90 is 3nm to 6nm, or PD 50 is 1 nm to 1.8 nm, and PD 90 is 3nm to 8nm, or PD 50 is 1 nm to 1.8 nm, and PD 90 is 3nm to 6nm, or PD 50 is 1 nm to 1.6 nm, and PD 90 can be 3 nm to 6 nm.
[0039] A pore fraction having a diameter in the range of larger mesopores can be advantageous because it facilitates electrolyte access to the electroactive material. Thus, pores having diameters in the range of 5 nm to 50 nm (i.e., larger mesopores) can optionally constitute at least 1%, at least 2%, at least 5%, or at least 10% of the total micropore and mesopore volume of the porous carbon scaffold.
[0040] The volume ratio of micropores to mesopores in the porous carbon skeleton can in principle be in the range of 100:0 to 50:50. Preferably, the volume ratio of micropores to mesopores is 90:10 to 55:45, or 90:10 to 60:40, or 85:15 to 65:35.
[0041] The pore size distribution of the porous carbon skeleton can be unimodal, bimodal, or multimodal. As used herein, the term "pore size distribution" refers to the cumulative total internal pore volume of the porous carbon skeleton. The pore size distribution relates to the distribution of pore sizes relative to the diameter of the pores. A bimodal or multimodal pore size distribution may be preferred because the proximity of pores with diameters up to 5 nm to larger diameter pores provides the advantage of efficient transport of ions through the porous network to the electroactive material. Thus, the particulate material has high ion diffusivity, improving the rate performance.
[0042] Optionally, the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 2.5 nm to 20 nm, preferably with a minimum in the pore size distribution in the range of 2 nm to 50 nm. More preferably, the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 2.5 nm to 15 nm, preferably with a minimum in the pore size distribution in the range of 2 nm to 5 nm.
[0043] Suitably, the bimodal or multimodal pore size distribution comprises a peak pore size in the micropore range and a peak pore size in the mesopore range that differ from each other by a factor of 5 to 20, more preferably about 10. For example, the porous carbon skeleton may have a bimodal pore size distribution having a peak pore size at 1.2 nm and a peak pore size at 12 nm.
[0044] The total volume of micropores and mesopores, as well as the pore size distribution of micropores and mesopores, were determined using quenched solid-state density functional theory (QSDFT) at 77 K for 10°C according to standard methodologies specified in ISO 15901-2 and ISO 15901-3. -6 The pore volume and pore size distribution are determined using nitrogen gas adsorption up to a relative pressure of p / p0. Nitrogen gas adsorption is a technique for characterizing the porosity and pore size distribution of a material by condensing a gas in the pores of a solid. As the pressure is increased, the gas condenses initially in the pores with the smallest diameter, until a saturation point is reached where all pores are filled with liquid. The nitrogen gas pressure is then reduced in steps to allow the liquid to evaporate from the system. The pore volume and pore size distribution can be determined by analysis of the adsorption and desorption isotherms and the hysteresis between them. Suitable devices for measuring the pore volume and pore size distribution by nitrogen gas adsorption include the TriStar II Porosity Analyzer and the TriStar II Plus porosity analyzer, as well as the Autosorb IQ porosity analyzer available from Quantachrome Instruments.
[0045] Nitrogen gas adsorption is effective for measuring the pore volume and pore size distribution of pores having diameters up to 50 nm, but becomes less reliable for pores of much larger diameters. Therefore, for the purposes of the present invention, nitrogen adsorption is used to determine the pore volume and pore size distribution of only pores having diameters up to 50 nm or less. As mentioned above, P 1 The value of is determined considering only pores with diameters up to 50 nm (i.e., only micropores and mesopores); similarly, PDn The value of is determined for the total volume of micropores and mesopores only.
[0046] Given the limitations of available analytical techniques, it is not possible to measure the pore volume and pore size distribution over the full range of micropores, mesopores, and macropores using a single technique. When the porous carbon skeleton contains macropores, the volume of pores in the range above 50 nm and up to 100 nm is referred to herein as P 2 cm 3 It is specified in terms of the value of / g and is measured by mercury intrusion porosimetry. 2 The value of refers to the pore volume of the porous carbon framework alone (i.e., in the absence of electroactive material or other materials occupying some or all of the pore volume).
[0047] To avoid any misunderstanding, P 2 The value of P considers only pores with diameters greater than 50 nm and up to 100 nm. 2 The value of P includes only the volume of macropores with diameters up to 100 nm. Any pore volume measured by mercury intrusion with pore diameters below 50 nm is not included in the P 2 is ignored for the purpose of determining the value of (nitrogen adsorption is used instead to characterize mesopores and micropores, as described above). The pore volume determined is assumed to be the interparticle porosity for the purposes of this invention, P 2 This pore volume is also not taken into account when determining the value of
[0048] Mercury intrusion porosimetry is a technique for characterizing the porosity and pore size distribution of a material by applying various levels of pressure to a sample of the material immersed in mercury. The pressure required to force mercury into the pores of the sample is inversely proportional to the pore size. Mercury intrusion values reported here were obtained according to ASTM UOP578-11, with a surface tension of mercury at room temperature, γ, of 480 mN / m, and a contact angle, φ, of 140°. The density of mercury at room temperature is 13.5462 g / cm 3There are many high-precision mercury intrusion instruments available commercially, such as the AutoPore IV series of automated mercury intrusion meters available from Micromeritics Instrument Corporation, USA. For a complete review of mercury intrusion methods, refer to "Analytical Methods in Fine Particle Technology, 1997, Micromeritics Instrument Corporation" by PA Webb and C. Orr (ISBN 0-9656783-0).
[0049] The macropore volume is preferably small compared to the micropore and mesopore volumes, and although some of the macropores may be useful to facilitate electrolyte access to the pore network, the advantages of the present invention are substantially obtained by accommodating the pore volume primarily to the micropores and smaller mesopores.
[0050] Thus, according to the present invention, the total volume of macropores in the porous carbon skeleton is determined by mercury intrusion porosimetry (P 2 cm 3 / g, where P 2 is preferably 0.2 x P 1 Less than or equal to 0.1 x P 1 Less than or equal to 0.05 x P 1 Less than or equal to 0.02 x P 1 Less than or equal to 0.01 x P 1 Less than or equal to 0.005 x P 1 It has the following values:
[0051] In a preferred embodiment, P 2 has a value of 0.3 or less, or 0.25 or less, or 0.20 or less, or 0.15 or less, or 0.1 or less, or 0.05 or less. As discussed above in relation to larger mesopores, a fraction of small pore volume in the macropore range can be advantageous to facilitate electrolyte access to the electroactive material.
[0052] The open pore network optionally includes a hierarchical pore structure, ie, a pore structure in which smaller pores branch off from larger pores and the pore sizes have some order.
[0053] It will be understood that intrusion techniques such as gas adsorption and mercury intrusion are only valid for determining the pore volume of pores that are accessible to nitrogen or mercury from the exterior of the porous carbon skeleton. 1 and P 2 ) should be understood to refer to the volume of open pores, i.e., pores accessible to fluids from outside the porous carbon framework. Completely enclosed pores that cannot be identified by nitrogen adsorption or mercury porosimetry shall not be considered herein in defining porosity values. Similarly, any pore volume located within pores small enough to be below the detection limit by nitrogen adsorption shall not be considered in defining porosity values. 1 is not taken into consideration in determining the value of
[0054] As used herein, the term "particle size" refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, where the volume of the particle is understood to include the volume of the pores within the particle. 50 " and "D 50 The term "particle size" refers to the median particle size on a volume basis, i.e., the diameter below which 50% by volume of the particle population lies. 10 " and "D 10 The term "particle size" refers to the 10th percentile median particle size on a volume basis, i.e., the diameter below which 10% by volume of the particle population lies. 90 " and "D 90 The term "particle size" refers to the volume-based 90th percentile median particle diameter, i.e., the diameter below which 90% of the particle population falls, by volume.
[0055] As used herein to define particle size distribution, "D n The term "PD" is used herein to define the pore size distribution, as described above.n " should be distinguished from the term "
[0056] Particle size and size distribution can be determined by conventional laser diffraction techniques in accordance with ISO 13320:2009. Laser diffraction is based on the principle that particles scatter light at angles that vary with the size of the particle, and a collection of particles produces a scattered light pattern defined by intensity and angle that can be correlated to particle size distribution. Many laser diffraction instruments are commercially available for quickly and reliably determining particle size distribution. Unless otherwise stated, particle size distribution measurements defined or reported herein are based on conventional Malvern Instruments laser diffraction instruments. The laser diffraction values reported herein were obtained using a Malvern Mastersizer™ 3000 particle size analyzer, which works by projecting a helium-neon gas laser beam through a transparent cell containing particles of interest suspended in an aqueous solution. The light beam striking the particles is scattered at angles inversely proportional to the particle size, and a photodetector array measures the light intensity at a number of predefined angles, and the intensities measured at the various angles are processed by a computer using standard theoretical principles to determine the particle size distribution. The laser diffraction values reported herein are obtained using a wet dispersion of the particles in distilled water. The refractive index of the particles is assumed to be 3.50 and the refractive index of the dispersant is assumed to be 1.330. The particle size distribution is calculated using the Mie scattering model.
[0057] Composite particle D 90 The particle size is preferably 9.5 μm or less, or 9 μm or less, or 8.5 μm or less, or 8 μm or less, or 7.5 μm or less, or 7 μm or less, or 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less.
[0058] The composite particles are in the range of D 0.5μm to 7μm. 50 Optionally, the composite particles may have a particle size D 50The particle size may be at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm.
[0059] Optionally, D for composite particles 50 The particle size may be 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less, or 3.5 μm or less.
[0060] For example, the composite particles may have a D in the range of 1 μm to 6.5 μm, or 1.5 μm to 6 μm, or 2 μm to 5.5 μm, or 2.5 μm to 5 μm, or 3 μm to 4.5 μm. 50 Particles within these size ranges and having the porosity and pore size distribution described herein are ideally suited for use in metal ion battery anodes because they are suitable for forming dense electrode layers that are dispersible in slurries, have structural integrity, retain capacity over repeated charge / discharge cycles, and have uniform thickness without structural degradation.
[0061] Composite particle D 10 The particle size is preferably at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 Maintaining particle size at or above 0.2 μm reduces the potential for undesirable agglomeration of submicron sized particles, improving dispersibility of the particulate material and improving capacity retention.
[0062] Composite particle D 99 The particle size is preferably 25 μm or less, or 20 μm or less, or 18 μm or less, or 15 μm or less, or 12 μm or less, or 10 μm or less, or 9 μm or less; Or 8 μm or less, or 7 μm or less, or 6 μm or less, or 5 μm or less.
[0063] The particle sizes preferably have a positive skew in the volume-based distribution, i.e., the volume-based distribution is asymmetric with a longer tail to the right. A positive skew in the volume-based particle size distribution is advantageous because it results in a higher natural packing than if all the particles were the same size, resulting in a denser electrode, thereby reducing the need for calendaring or other physical densification processes.
[0064] The composite particles preferably have a narrow particle size distribution span. For example, the particle size distribution span (D 90 -D 10 ) / D 50 (defined as) is preferably 8 or less, and optionally can be 5 or less, or 4 or less, or 3 or less. Preferably, the particle size distribution span is at least 1, and optionally can be at least 1.5, or at least 2.
[0065] The composite particles preferably have a spheroidal shape. Spheroidal particles as defined herein can include both spherical and spheroidal particles, and the shape of the composite particles of the present invention can be suitably defined by reference to the sphericity and aspect ratio of the particles of the present invention. It has been found that spheroidal particles are particularly suitable for dispersion in slurries without forming agglomerates. It has also been found that the use of porous spheroidal particles surprisingly provides additional strength improvements when compared to irregularly shaped porous particles and porous particle fragments.
[0066] The sphericity of an object is conventionally defined as the ratio of the surface area of the object to that of a sphere, where the object and the sphere have the same volume. However, in practice, it is difficult to measure the surface area and volume of individual micron-scale particles. However, by scanning electron microscopy (SEM) and dynamic image analysis, where the shadow cast by the particle is recorded using a digital camera, highly accurate two-dimensional projection images of micron-scale particles can be obtained. The term "sphericity" as used herein shall be understood as the ratio of the area of the particle projection to the area of a circle, where the particle projection and the circle have the same circumference. Thus, for an individual particle, the sphericity S may be defined as follows:
number
number
[0067] The term "spheroidal" as used herein as applied to the composite particles of the invention shall be understood to refer to materials having an average sphericity of at least 0.70. The porous particles of the invention preferably have an average sphericity of at least 0.85, or at least 0.90, or at least 0.92, or at least 0.93, or at least 0.94, or at least 0.95. The porous spheroidal particles may optionally have an average sphericity of at least 0.96, or at least 0.97, or at least 0.98, or at least 0.99.
[0068] Sphericity within these preferred ranges is preferably combined with a positive skew in the volume-based particle size distribution to optimally pack the particles into a dense electrode layer while reducing the need for physical densification, for example by calendaring.
[0069] It will be appreciated that the circumference and area of a two-dimensional particle projection image will depend on the particle orientation for any particle that is not perfectly spheroidal. However, the effect of particle orientation can be countered by reporting sphericity and aspect ratio as average values obtained from multiple particles with random orientation. Many SEM and dynamic image analyzers are commercially available that can rapidly and reliably determine the sphericity and aspect ratio of particulate materials. Unless otherwise stated, sphericity values specified or reported herein are measured by a CamSizer XT particle analyzer manufactured by Retsch Technology GmbH. The CamSizer XT is a dynamic image analyzer that can obtain highly accurate distributions of size and shape of particulate materials for sample volumes between 100 mg and 100 g, and properties such as average sphericity and aspect ratio can be calculated directly with this instrument.
[0070] The porous carbon skeleton may comprise crystalline or amorphous carbon, or a mixture of amorphous and crystalline carbon. The porous carbon skeleton may be either a hard or a soft carbon skeleton, and may suitably be obtained by known procedures, including pyrolysis of polymers.
[0071] As used herein, the term "hard carbon" refers to carbon atoms that are primarily distributed in nanoscale polyaromatic domains. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. The polyaromatic domains are cross-linked by chemical bonds, e.g., COC bonds. Because the polyaromatic domains are chemically cross-linked, the hard carbon cannot be converted to graphite at high temperatures. The high G band (approx. 1600 cm) in the Raman spectrum -1), hard carbon has graphite-like properties. However, the high D band in the Raman spectrum (approximately 1350 cm -1 ), carbon is not entirely graphite-like.
[0072] The term "soft carbon" as used herein also refers to carbon atoms that are primarily dispersed in polyaromatic domains having dimensions in the range of 5 nm to 200 nm. 2 It refers to a disordered carbon matrix that adopts a hybridized (three-way bond) state. In contrast to hard carbon, the polyaromatic domains in soft carbon are not cross-linked by chemical bonds but are held together by intermolecular forces; that is, at high temperatures, soft carbon can be graphitized. The porous carbon skeleton preferably has at least 50% sp 2 For example, the porous carbon skeleton preferably contains 50% to 98% sp 2 Hybrid carbon, 55%-95% sp 2 Hybrid carbon, 60%-90% sp 2 Hybrid carbon, or 70% to 85% sp 2 It may contain hybridized carbon.
[0073] A variety of different materials can be used to create suitable porous carbon scaffolds. Examples of organic materials that can be used include plant biomass, including lignocellulosic materials (coconut shells, rice husks, wood, etc.), and fossil carbon sources such as coal. Examples of polymeric materials that form porous carbon scaffolds upon pyrolysis include phenolic resins, novolac resins, pitch, melamine, polyacrylates, polystyrene, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and various copolymers that contain monomer units of acrylates, styrene, α-olefins, vinylpyrrolidone, and other ethylenically unsaturated monomers. Depending on the starting materials and the conditions of the pyrolysis process, a variety of different hard carbon materials are available in the art.
[0074] To increase the volume of mesopores and micropores, the porous carbon framework can be subjected to a chemical or gas activation process. A suitable activation process is thermal It involves contacting the decomposed carbon with one or more of oxygen, steam, CO, CO2, and KOH at a temperature in the range of 600°C to 1000°C.
[0075] Mesopores can also be obtained by known templating processes using extractable pore formers such as MgO and other colloidal or polymeric templates, which can be removed by thermal or chemical means after pyrolysis or activation.
[0076] The porous carbon skeleton is preferably at least 750 mm 2 / g, or at least 1000m 2 / g, or at least 1250m 2 / g, or at least 1500m 2 / g. The term "BET surface area" as used herein should be taken to refer to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules onto a solid surface using the Brunauer-Emmett-Teller theory according to ISO 9277. Preferably, the BET surface area of the conductive porous particle scaffold is greater than 4000 m 2 / g or less, or 3500m 2 / g or less, or 3250m 2 / g or less, or 3000m 2 / g or less. In some cases, the particulate materials of the present invention may include pores that are completely enclosed by the electroactive material such that the voids do not provide access to the electrolyte.
[0077] The electroactive material is preferably selected from silicon, tin, germanium, and aluminum, and mixtures thereof. A preferred electroactive material is silicon. The electroactive material may optionally include small amounts of one or more dopants. Suitable dopants include boron and phosphorus, other n-type or p-type dopants, or nitrogen. Preferably, the dopants are present in a total amount of 2% by weight or less, based on the total amount of the electroactive material (e.g., silicon) and the dopant(s).
[0078] The amount of electroactive material in the composite particles of the invention is preferably selected such that the electroactive material occupies no more than about 55% of the internal pore volume of the porous carbon skeleton (in the uncharged state). This is referred to herein as the "filling factor" of the electroactive material within the porous carbon skeleton. The electroactive material preferably occupies about 25% to about 45% of the internal pore volume of the porous carbon skeleton, more preferably about 25% to 40% of the internal pore volume of the porous carbon skeleton. Within these preferred ranges, the pore volume of the porous carbon skeleton will be effective to accommodate the expansion of the electroactive material upon charging and discharging, and excess pore volume that does not contribute to the volumetric capacity of the particulate material is avoided. However, the amount of electroactive material is also not so high as to prevent effective lithiation due to insufficient metal ion diffusion rate or insufficient expansion volume resulting in mechanical resistance to lithiation.
[0079] The weight ratio of the electroactive material to the porous carbon skeleton can be determined by elemental analysis. Elemental analysis is used to determine the weight percentage of both the electroactive material and carbon in the composite particle. Optionally, the amount of hydrogen, nitrogen, and oxygen can also be determined by elemental analysis. Preferably, elemental analysis is also used to determine the weight percentage of carbon (and optionally hydrogen, nitrogen, and oxygen) in the porous carbon skeleton only. Determining the weight percentage of carbon in the porous carbon skeleton only takes into account the possibility that the porous carbon skeleton contains small amounts of heteroatoms in its molecular framework. Both measurements taken together can reliably determine the weight percentage of the electroactive material to the entire porous carbon skeleton.
[0080] The weight percentage of electroactive materials (e.g., silicon, germanium, tin, and aluminum) is preferably determined by ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy). Many ICP-OES instruments are commercially available, such as the 7000 series. The carbon content (and optionally hydrogen, nitrogen, and oxygen content) in the composite particles and in the porous carbon skeleton alone is preferably determined by IR absorption. A suitable instrument for determining content is the TruSpec™ Micro elemental analyzer available from Leco Corporation.
[0081] The weight ratio of electroactive material to the porous carbon skeleton is a function of the available pore volume, the required loading, and the density of the electroactive material.
[0082] When the electroactive material is silicon, the weight ratio of silicon to the porous carbon skeleton is preferably [0.5×P 1 ~1.7×P 1 ]:1, where P 1 is cm 3 The total micropore / mesopore volume is expressed as a value measured in units of P / g. 1 By defining the weight ratio of silicon based on the value of [0.5×P], the volume fraction of the pore volume occupied by silicon is controlled within a specific limit. In other words, when the weight ratio of silicon to the porous carbon skeleton is [0.5×P], the volume fraction of the pore volume occupied by silicon is controlled within a specific limit. 1 ~1.7×P 1 ]:1, the volume of silicon in the composite particles corresponds to approximately 20%-55% of the total micropore / mesopore volume of the porous carbon skeleton.
[0083] Optionally, the weight ratio of silicon to the porous carbon skeleton is [0.5×P 1 ~1.3×P 1 ]:1. More preferably, the weight ratio of silicon to porous carbon skeleton may be in the range of [0.55×P 1~1.1×P 1 ]:1 range or [0.6×P 1 ~1.1×P 1 ]:1 range or [0.6×P 1 ~1×P 1 ]:1 range or [0.6×P 1 ~0.95×P 1 ]:1 range or [0.6×P 1 ~0.9×P 1 ]:1 range, or [0.65×P 1 ~0.9×P 1 ]:1 range, or [0.65×P 1 ~0.85×P 1 ]:1 range, or [0.65×P 1 ~0.8×P 1 ]:1 range, or [0.7×P 1 ~0.8×P 1 ]:1.
[0084] Optionally, the weight ratio of silicon to the porous carbon skeleton is [1×P 1 ~1.7×P 1 More preferably, the weight ratio of silicon to the porous carbon skeleton can be in the range of [1.1×P 1 ~1.7×P 1 ]:1 range, or [1.1×P 1 ~1.65×P 1 ]:1 range, or [1.1×P 1 ~1.6×P 1 ]:1 range, or [1.15×P 1 ~1.6×P 1 ]:1 range, or [1.15×P 1 ~1.55×P 1 ]:1 range, or [1.15×P 1 ~1.5×P 1 ]:1 range or [1.2×P 1 ~1.5×P 1 ]:1 range or [1.25×P 1 ~1.5×P 1 ]:1 range, or [1.3×P 1 ~1.5×P 1 ]:1.
[0085] Preferably at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the mass of electroactive material in the composite particles is located within the interior pore volume of the porous carbon skeleton, such that there is little or no electroactive material located on the outer surface of the composite particles.
[0086] The particulate material of the invention may be further characterized by its performance by thermogravimetric analysis (TGA) in air: preferably 10% or less, more preferably 5% or less, more preferably 2% or less of the silicon content of the particulate material is unoxidized at 800° C. when the particulate material is analyzed by TGA in air at a temperature ramp rate of 10° C. / min.
[0087] The amount of unoxidized silicon is determined by derivation from TGA traces specific to these materials. A mass increase between about 300 °C and 500 °C corresponds to the initial oxidation of silicon to SiO2, followed by a mass loss between about 500 °C and 600 °C as carbon is oxidized to CO2 gas. Above about 600 °C there is a further mass increase corresponding to the continued conversion of silicon to SiO2, which increases towards an asymptotic value above 1000 °C as the oxidation of silicon becomes complete.
[0088] For the purposes of this analysis, any mass increase above 800°C is attributed to the conversion of silicon to SiO2. The total mass at the end of oxidation is assumed to be SiO2. This allows the proportion of unoxidized silicon at 800 °C to be determined as a percentage of the total amount of silicon according to the following formula: Z = 1.875 × [(M f -M 800 ) / M f ]×100% (where Z is the proportion of unoxidized silicon at 800°C, M f is the mass of the sample upon completion of oxidation, and M 800 is the mass of the sample at 800°C).
[0089] Without being bound by theory, it is understood that the temperature at which silicon oxidizes under TGA corresponds roughly to the length scale of the oxide film on silicon, since the diffusion of oxygen atoms through the oxide layer is thermally activated. The size of the silicon nanostructures and their location limit the length scale of the oxide film thickness. It is therefore understood that silicon deposited in micropores and mesopores oxidizes at a lower temperature than silicon deposits on the particle surface, since the oxide film present on these structures is necessarily thinner. Thus, preferred materials according to the invention show substantially complete oxidation of silicon at low temperatures, consistent with the smaller length scale of silicon nanostructures located in micropores and smaller mesopores. For the purposes of the present invention, it is assumed that the oxidation of silicon at 800° C. is silicon on the outer surface of the porous carbon skeleton.
[0090] The silicon is preferably amorphous silicon, which is believed to have better performance as an electroactive material. The morphology of the silicon can be determined by known procedures using X-ray diffraction (XRD).
[0091] The volume of the micropores and mesopores of the composite particles (i.e., in the presence of the electroactive material), as measured by nitrogen gas adsorption, is preferably less than or equal to 0.15×P 1 Less than or equal to 0.10 x P 1 Less than or equal to 0.05 x P 1 Less than or equal to 0.02 x P 1 The following is the result.
[0092] The composite particles preferably have a low total oxygen content. Oxygen may be present in the composite particles, for example, as part of the porous carbon skeleton or as an oxide layer on any exposed electroactive material surface. The total oxygen content of the composite particles is preferably less than 15% by weight, more preferably less than 10% by weight, more preferably less than 5% by weight, for example less than 2% by weight, or less than 1% by weight, or less than 0.5% by weight.
[0093] The particulate material of the present invention is preferably 300 ml2 / g or less, or 250m 2 / g or less, or 200m 2 / g or less, or 150m 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 / g or less, or 10m 2 The BET surface area is preferably at least 0.1 m2 / g. Typically, a small BET surface area is preferred to minimize the formation of a solid electrolyte interfacial (SEI) layer on the surface of the composite particles during the first charge-discharge cycle of an anode comprising the particulate material of the present invention. However, an excessively small BET surface area leads to unacceptably low charge rates and capacities due to the inaccessibility of the bulk of the electroactive material to metal ions in the surrounding electrolyte. For example, the BET surface area is preferably at least 0.1 m2 / g. 2 / g, or at least 1m 2 / g, or at least 2m 2 / g, or at least 5m 2 / g. For example, the BET surface area is 2 / g~25m 2 / g, more preferably 2m 2 / g~15m 2 / g range.
[0094] The particulate material of the present invention typically has a specific charge capacity of 1200 mAh / g to 2340 mAh / g upon initial lithiation. Preferably, the particulate material of the present invention has a specific charge capacity of at least 1400 mAh / g upon initial lithiation.
[0095] The composite particles of the present invention are preferably prepared by chemical vapor infiltration (CVI) of a silicon-containing precursor into the pore structure of a porous carbon skeleton. As used herein, CVI refers to a process in which a gaseous silicon-containing precursor is pyrolyzed on a surface to form elemental silicon and gaseous by-products on the surface.
[0096] Suitable gaseous silicon-containing precursors include silane (SiH4), silane derivatives (e.g., disilane, trisilane, and tetrasilane), and trichlorosilane (SiHCl3). The silicon-containing precursor can be used in pure form or, more commonly, as a dilute mixture with an inert carrier gas such as nitrogen or argon. For example, the silicon-containing precursor can be used in an amount ranging from 0.5% to 20% by volume, or 1% to 10% by volume, or 1% to 5% by volume, based on the total volume of the silicon-containing precursor and the inert carrier gas. The CVI process is preferably carried out at a total pressure of 101.3 kPa (i.e., 1 atm), with a low partial pressure of the silicon precursor, and the remaining partial pressure being atmospheric, using an inert padding gas such as hydrogen, nitrogen, or argon. Deposition temperatures in the range of 400° C. to 700° C. are used, for example, 400° C. to 550° C., or 400° C. to 500° C., or 400° C. to 450° C., or 450° C. to 500° C. The CVI process is suitably carried out in a fixed bed reactor, a fluidized bed reactor (including an entrained bed reactor), or a rotary kiln.
[0097] As an example of the fixed bed reactor method, 1.8 g of particulate porous scaffolds were placed on a stainless steel plate with a constant thickness of 1 mm along its length. The plate was then placed inside a 60 mm outer diameter stainless steel tube, and the gas inlet and outlet lines were placed in the hot zone of a retort furnace. The furnace tube was purged with nitrogen gas for 30 minutes at room temperature, after which the sample temperature was increased to 450°C-500°C. The flow rate of nitrogen gas was adjusted to ensure a gas residence time of at least 90 seconds in the furnace tube, and maintained at that rate for 30 minutes. The gas supply was then switched from nitrogen to a mixture of monosilane in nitrogen at a concentration of 1.25% by volume. The monosilane charge was made over a period of 5 hours, with the reactor pressure maintained at 101.3 kPa (1 atm). After the charge was completed, the gas flow rate was kept constant while nitrogen was used to purge the silane from the furnace. The furnace was purged under nitrogen for 30 minutes, and then cooled to room temperature over several hours. The atmosphere is then gradually switched to air over a period of 2 hours by switching the gas flow from nitrogen to air from a compressed air supply.
[0098] The particulate material of the present invention may optionally include a conductive carbon coating. Preferably, the conductive carbon coating may be obtained by a chemical vapor deposition (CVD) method. CVD is a methodology known in the art and involves pyrolysis of a volatile carbon-containing gas (e.g., ethylene) on the surface of the particulate material. Alternatively, the carbon coating may be formed by depositing a solution of a carbon-containing compound on the surface of the particulate material, followed by pyrolysis. The conductive carbon coating has sufficient permeability to allow lithium access to the interior of the composite particle without excessive resistance so as not to degrade the rate performance of the composite particle. For example, the thickness of the carbon coating may preferably be in the range of 2 nm to 30 nm. The carbon coating may optionally be porous and / or may only partially cover the surface of the composite particle.
[0099] The carbon coating smoothes out any surface imperfections and reduces the remaining microporosity of the surface. The carbon coating has the advantage of further reducing the BET surface area of the particulate material, thereby further reducing first cycle losses. The carbon coating also improves the electrical conductivity of the surface of the composite particles, reducing the need for conductive additives in the electrode composition, and provides an optimal surface for the formation of a stable SEI layer, improving capacity retention upon cycling.
[0100] According to the first aspect of the present invention, there are further provided particulate materials according to the following aspects 1-1 to 1-16.
[0101] Aspect 1-1: (i)P 1 is in the range of 0.6 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.
[0102] Aspect 1-2: (i)P 1 is in the range of 0.6 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.
[0103] Aspects 1-3: (i)P 1 is in the range of 0.6 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.
[0104] Aspects 1-4: (i)P1 is in the range of 0.6 to 1.4, (ii)PD 50 The pore size is in the range of 0.8 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.
[0105] Aspects 1-5: (i)P 1 is in the range of 0.7 to 1.2, (ii)PD 50 The pore size is in the range of 1 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.
[0106] Aspects 1-6: (i)P 1 is in the range of 0.7 to 1.2, (ii)PD 50 The pore size is in the range of 1 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.
[0107] Aspects 1-7: (i)P 1 is in the range of 0.7 to 1.2, (ii)PD 50 The pore size is in the range of 1 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.
[0108] Aspects 1-8: (i)P 1 is in the range of 0.7 to 1.2, (ii)PD 50 The pore size is in the range of 1 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.
[0109] Aspect 1-9: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.
[0110] Aspects 1-10: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.
[0111] Aspect 1-11: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.
[0112] Aspect 1-12: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 2 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.
[0113] Aspect 1-13: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.8 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 18 μm. A particulate material according to a first aspect of the present invention.
[0114] Aspect 1-14: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.8 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 1 μm to 12 μm. A particulate material according to a first aspect of the present invention.
[0115] Aspect 1-15: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.8 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 2 μm to 8 μm. A particulate material according to a first aspect of the present invention.
[0116] Aspect 1-16: (i)P 1 is in the range of 0.7 to 1, (ii)PD 50 The pore size is in the range of 1.2 nm to 1.8 nm, (iii) D of the porous carbon framework 50 The particle size is in the range of 3 μm to 6 μm. A particulate material according to a first aspect of the present invention.
[0117] It is to be understood that, according to the present invention, the preferred / optional features disclosed herein with respect to the first aspect of the invention, which are within the scope of the above-mentioned aspects 1-1 to 1-16, are also to be considered as preferred / optional features of aspects 1-1 to 1-16. Similarly, any features of dependent claims falling within the scope of the above-mentioned embodiments 1-1 to 1-16 should be construed as if those claims were dependent on embodiments 1-1 to 1-16.
[0118] In a second aspect of the invention, there is provided a composition comprising a particulate material according to the first aspect of the invention and at least one other component. The particulate material used to make the composition of the second aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate material according to any of aspects 1-1 to 1-16. In particular, the particulate material of the first aspect of the invention may be used as a component of an electrode composition.
[0119] There is thus provided a composition comprising a particulate material according to the first aspect of the invention and at least one other component selected from (i) a binder, (ii) a conductive additive, and (iii) an additional particulate electroactive material. The composition of the invention is useful as an electrode composition and may thus be used to form an active layer on an electrode.
[0120] The electrode composition may optionally be a hybrid electrode composition comprising the particulate material according to the first aspect of the invention and at least one additional particulate electroactive material. Examples of additional particulate electroactive materials include graphite, hard carbon, silicon, germanium, gallium, aluminum, and lead. The at least one additional particulate electroactive material is preferably selected from graphite and hard carbon. The at least one additional particulate electroactive material is most preferably graphite.
[0121] The particulate material of the present invention may comprise 0.5% to 99.5% by weight of the total dry weight of the electrode composition (i.e., the total dry weight of the particulate material of the present invention and any additional particulate electroactive materials, binders and / or conductive additives). More preferably, the electrode composition comprises a high loading of the particulate material of the present invention. For example, the particulate material of the present invention may preferably comprise at least 50% by weight, or at least 55% by weight, or at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight of the total dry weight of the electrode composition.
[0122] The electrode composition may optionally include a binder. The binder functions to adhere the electrode composition to the current collector and maintain the integrity of the electrode composition. Examples of binders that may be used according to the present invention include polyvinylidene fluoride (PVDF), polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, carboxymethyl cellulose (CMC), modified carboxymethyl cellulose (mCMC), sodium carboxymethyl cellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, styrene-butadiene rubber (SBR), and polyimides. The electrode composition may include a mixture of binders. Preferably, the binder includes a polymer selected from polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, SBR, and CMC.
[0123] The binder may suitably be present in an amount of from 0.5% to 20% by weight, preferably from 1% to 15% by weight, and most preferably from 2% to 10% by weight, based on the total dry weight of the electrode composition.
[0124] The binder may optionally be present in combination with one or more additives that modify the properties of the binder, such as crosslinking promoters, coupling agents, and / or adhesion promoters.
[0125] The electrode composition may optionally include one or more conductive additives. Preferred conductive additives are non-electroactive materials that are included to improve electrical conductivity between the electroactive components of the electrode composition and between the electroactive components of the electrode composition and the current collector. The conductive additives may be suitably selected from carbon black, carbon fibers, carbon nanotubes, graphene, acetylene black, ketjen black, metal fibers, metal powders, and conductive metal oxides. Preferred conductive additives include carbon black and carbon nanotubes.
[0126] The one or more conductive additives may suitably be present in a total amount of from 0.5% to 20% by weight, preferably from 1% to 15% by weight, and most preferably from 2% to 10% by weight, based on the total dry weight of the electrode composition.
[0127] In a third aspect, the present invention provides an electrode comprising a particulate material as defined with reference to the first aspect of the invention in electrical contact with a current collector. The particulate material used to prepare the electrode of the third aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate material according to any of aspects 1-1 to 1-16.
[0128] The term current collector as used herein refers to any conductive substrate capable of conducting electrical current to and from the electroactive particles in the electrode composition. Examples of materials that can be used as current collectors include copper, aluminum, stainless steel, nickel, titanium, and sintered carbon. Copper is a preferred material. Current collectors are typically in the form of a foil or mesh having a thickness of 3 μm to 500 μm. The particulate material of the present invention can be applied to one or both sides of the current collector, preferably in a thickness ranging from 10 μm to 1 mm, for example, from 20 μm to 500 μm, or from 50 μm to 200 μm.
[0129] Preferably, the electrode comprises an electrode composition as defined with reference to the second aspect of the invention in electrical contact with a current collector. The electrode composition may have any of the features described as preferred or optional in relation to the second aspect of the invention.
[0130] The electrode of the third aspect of the invention may suitably be prepared by combining the particulate material of the invention (optionally in the form of an electrode composition of the invention) with a solvent and optionally one or more viscosity modifying additives to form a slurry. The slurry is then cast onto the surface of a current collector and the solvent is removed to form an electrode layer on the surface of the current collector. Further steps such as heat treatment to harden any binder and / or calendaring the electrode layer may optionally be carried out. The electrode layer suitably has a thickness in the range of 20 μm to 2 mm, preferably 20 μm to 1 mm, preferably 20 μm to 500 μm, preferably 20 μm to 200 μm, preferably 20 μm to 100 μm, preferably 20 μm to 50 μm.
[0131] Alternatively, the slurry can be formed into a free-standing film or mat comprising the particulate material of the present invention, for example, by casting the slurry onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat has the form of a free-standing agglomerate, which can then be adhered to a current collector by known methods.
[0132] The electrode of the third aspect of the invention can be used as the anode of a metal-ion battery. Thus, in a fourth aspect, the invention provides a rechargeable metal-ion battery comprising an anode comprising an electrode as described above, a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions, and an electrolyte between the anode and the cathode. The particulate materials used to prepare the battery of the fourth aspect of the invention can be any of the preferred or optional particulate materials as described in relation to the first aspect of the invention. The particulate material may have any of the characteristics described above and may be a particulate material according to any of the aspects 1-1 to 1-16.
[0133] The metal ions are preferably lithium ions. More preferably, the rechargeable metal ion battery of the present invention is a lithium ion battery and the cathode active material is capable of releasing lithium ions.
[0134] The cathode active material is preferably a metal oxide-based composite material. Examples of suitable cathode active materials include LiCoO2, LiCo 0.99 Al 0.01 O2, LiNiO2, LiMnO2, LiCo 0.5 Ni 0.5 O2, LiCo 0.7 Ni 0.3 O2, LiCo 0.8 Ni 0.2 O2, LiCo 0.82 Ni 0.18 O2, LiCo 0.8 Ni 0.15 Al 0.05 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2 and LiNi 0.33 Co 0.33 Mn 0.34 O2. The cathode current collector usually has a thickness of 3 μm to 500 μm. Examples of materials that can be used as the cathode current collector include aluminum, stainless steel, nickel, titanium, and sintered carbon.
[0135] The electrolyte is preferably a non-aqueous electrolyte containing a metal salt, such as a lithium salt, and may include, but is not limited to, a non-aqueous electrolyte, a solid electrolyte, and an inorganic solid electrolyte. Examples of non-aqueous electrolytes that may be used include aprotic organic solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethylsulfoxide, 1,3-dioxolane, formamide, dimethylformamide, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, sulfolane, methylsulfolane, and 1,3-dimethyl-2-imidazolidinone.
[0136] Examples of organic solid electrolytes include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate ester polymers, polyester sulfides, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionically dissociable groups.
[0137] Examples of inorganic solid electrolytes include nitrides, halides, and sulfides of lithium salts, such as Li5NI2, Li3N, LiI, LiSiO4, Li2SiS3, Li4SiO4, LiOH, and Li3PO4.
[0138] The lithium salt is preferably soluble in the selected solvent or mixture of solvents. Examples of suitable lithium salts include LiCl, LiBr, LiI, LiClO4, LiBF4, LiBC4O8, LiPF6, LiCF3SO3, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, and CF3SO3Li.
[0139] When the electrolyte is a non-aqueous organic solution, the metal ion battery preferably includes a separator inserted between the anode and the cathode. The separator is typically formed of an insulating material having high ion permeability and high mechanical strength. The separator typically has a pore size of 0.01 μm to 100 μm and a thickness of 5 μm to 300 μm. An example of a suitable electrode separator is a microporous polyethylene film.
[0140] The separator may be replaced with a polymer electrolyte material, in which case the polymer electrolyte material is present in both the composite anode layer and the composite cathode layer. The polymer electrolyte material may be a solid polymer electrolyte or a gel-type polymer electrolyte.
[0141] In a fifth aspect, the present invention provides the use of a particulate material as defined with reference to the first aspect of the invention as an anode active material. Preferably, the particulate material has the form of an electrode composition as defined with reference to the second aspect of the invention, and most preferably the electrode composition comprises one or more additional particulate electroactive materials as defined above. The particulate material used according to the fifth aspect of the invention may have any of the features described as preferred or optional in relation to the first aspect of the invention and may be a particulate material according to any of aspects 1-1 to 1-16. [Brief description of the drawings]
[0142] [Figure 1] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0143] Example 1 Porous carbon skeleton particles (activated carbon particles) having the properties shown in Table 1 were prepared.
[0144] [Table 1]
[0145] Silicon-carbon composite particles were made by depositing silicon within the pores of the porous carbon skeleton particles of Table 1 using monosilane gas in a fixed bed reactor at 475° C. as described herein.
[0146] Example 2 - Compression Test The resistance of the particulate material of the present invention to mechanical degradation was evaluated using a flat indenter with a diameter of 50 μm, test forces ranging from 9.8 mN to 4903 mN, and a test pressure of 7.75 mN s -1 The analysis was carried out by performing compression tests on single particles using a high-precision microcompression tester (Shimadzu Corporation (trademark) model MCT-510) equipped with a loading rate of 100 s.
[0147] Particles of various sizes were selected from various composite particle samples (samples A1 to A4 were obtained from scaffold A, while samples B1 and C1 were obtained from scaffolds B and C, respectively). For each particle size of interest, at least five particles with particle sizes close to the particle size of interest were analyzed. Particle sizes were measured by the sample dimensioning function of the model MCT-510 using the average of the geometric mean diameter and length of the sample using an image from above (obtained by optical microscopy). Each particle was clamped between a flat indenter and a pressure plate below it before applying a test force of 9.8 mN to 4900 mN to the sample and increasing the load at the loading rate mentioned above. A sudden increase in displacement indicates that fracture has occurred in that particle. The force applied at the time of initial fracture is taken as the particle crushing force. The crushing pressure is calculated by dividing the applied crushing force by the particle area projected on the indenter face. The average crushing pressure of multiple samples with various particle sizes for each composite was taken as the final crushing pressure. The results are shown in Table 2.
[0148] [Table 2]
[0149] It will be appreciated that the crushing pressure of individual particles is subject to large variations due to unpredictable differences between individual particles (e.g., the presence of defects, the shape of the particle in contact with the indenter). To offset this inherent variability, Applicant has developed a P 1 The average crush pressure obtained from various particles having microporosity ranging from 0.54 to 0.78, and silicon weight percentages ranging from 45% to 59% was also calculated. Results collected from multiple experiments with particle sizes of about 3 μm, 5 μm, 8 μm, 12 μm, and 15 μm are shown in Table 3 and clearly show the relationship between particle size distribution and robustness of the composite particles. Tables 2 and 3 show that particles of the present invention having particle sizes of 8 μm or less have a crush pressure averaged over five particles of at least 250 MPa when measured by the microcompression tester described herein.
[0150] [Table 3]
[0151] Example 3 - Electrochemical testing Test coin cells were prepared as described above using both >10 μm and <10 μm D9 The negative electrode was fabricated using a silicon-carbon particulate material having a particle size of 0.0. A dispersion of Super P (conductive carbon) in CMC binder was mixed in a Thinky™ mixer. Silicon-carbon particulate material was added to this conductive dispersion and mixed in a Thinky™ mixer for 30 minutes. SBR binder was then added to give a CMC:SBR ratio of 1:1 to obtain a slurry with a weight ratio of particulate silicon-carbon:CMC / SBR binder:conductive carbon of 70:16:14. The slurry was mixed in a Thinky™ mixer for an additional 30 minutes, then coated on a copper substrate (current collector) with a thickness of 10 μm, dried at 50° C. for 10 minutes, and then further dried at 120° C. to 180° C. for 12 hours to form an electrode with an active layer on the copper substrate.
[0152] Full cell manufacturing A full coin cell was fabricated using a circular negative electrode with a radius of 0.8 cm cut from this electrode along with a porous polyethylene separator and a nickel manganese cobalt (NMC532) positive electrode. The positive and negative electrodes were designed to form a balanced pair such that the target capacity ratio of these electrodes was approximately 0.9 (positive:negative). An electrolyte consisting of 1 M LiPF6 in a 7:3 EMC / FEC (ethylene methyl carbonate / fluoroethylene carbonate) solution containing 3 wt% vinylene carbonate was then added to the cell before sealing.
[0153] The full coin cell was cycled as follows: The anode was lithiated by applying a constant current at a rate of C / 25 with a cutoff voltage of 4.3V. Once the cutoff voltage was reached, a constant voltage of 4.3V was applied until a cutoff current of C / 100 was reached. The cell was then allowed to rest for 10 minutes in the lithiated state. The anode was then delithiated with a constant current of C / 25 with a cutoff voltage of 2.75V. The cell was then allowed to rest for 10 minutes. After this initial cycle, the anode was lithiated with a constant current of C / 2 with a cutoff voltage of 4.3V, followed by a constant voltage of 4.3V with a cutoff current of C / 40 and a rest time of 5 minutes. The anode was then delithiated with a constant current of C / 2 with a cutoff voltage of 2.75V. This was then repeated for the desired number of cycles. The discharge capacity in mAh / g (per gram of silicon-carbon composite particles) for the three test cells is plotted in FIG. 1.
[0154] All three silicon-carbon materials used in the negative electrodes have similar weight percent silicon and therefore similar initial discharge capacity. Each material also has less than 10% unoxidized silicon content at 800° C. when analyzed by TGA as described herein. Samples X and Y have D of less than 10 μm. 90 Particle size (and D of 3.2 μm and 4.1 μm, respectively) 50 The sample Z has a D of 6.5 μm and exhibits a good capacity retention rate within the range of the present invention. 50 Particle size and D outside the scope of the present invention 90The particles have a particle size and exhibit an increased rate of volume loss, as demonstrated above, but it is seen that these results are consistent with the hypothesis that the small particle size and high microporosity of the particles of the present invention allow them to better accommodate not only compressive stresses, but also stresses due to the expansion of the silicon over multiple cycles.
Claims
1. A particulate material comprising a plurality of composite particles, the composite particles comprising: (a) a porous carbon framework containing micropores and / or mesopores, The micropores and mesopores have a total pore volume of P measured by gas adsorption. 1 cm 3 / g, where P 1 represents a natural number having a value of at least 0.6, PD measured by gas adsorption 50 a porous carbon skeleton having pores with a diameter of 2 nm or less; (b) an electroactive material located within the micropores and / or mesopores of the porous carbon framework; Including, The composite particles have a D of 10 μm or less. 90 A particulate material having a particle size.
2. P 1 2. The particulate material of claim 1 , wherein R has a value of at least 0.65, or at least 0.7, or 0.75, or at least 0.8, or at least 0.85, or at least 0.9, or at least 0.95, or at least, or at least 1.05, or at least 1.1, or at least 1.15, or at least 1.
2.
3. P 1 3. The particulate material of claim 1 or 2, wherein R has a value of 2.4 or less, or 2.2 or less, or 2 or less, or 1.8 or less, or 1.6 or less, or 1.5 or less, or 1.4 or less, or 1.3 or less, or 1.2 or less, or 1.1 or less, or 1.0 or less, or 0.9 or less.
4. The PD of the porous carbon skeleton 50 4. A particulate material according to any one of claims 1 to 3, wherein the pore size is 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less, or 1.2 nm or less, or 1 nm or less.
5. The PD of the porous carbon skeleton 60 5. A particulate material according to any one of claims 1 to 4, wherein the pore size is 3nm or less, or 2.5nm or less, or 2nm or less, or 1.8nm or less, or 1.6nm or less, or 1.4nm or less, or 1.2nm or less.
6. The PD of the porous carbon skeleton 70 6. The particulate material of any one of claims 1 to 5, wherein the pore size is 3.5 nm or less, or 3 nm or less, or 2.5 nm or less, or 2.2 nm or less, or 2 nm or less, or 2.5 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less, or 1.4 nm or less.
7. The PD of the porous carbon skeleton 80 7. The particulate material according to any one of claims 1 to 6, wherein the pore size is 5 nm or less, or 4.5 nm or less, or 4 nm or less, or 3.5 nm or less, or 3 nm or less, or 2.5 nm or less, or 2.2 nm or less, or 2 nm or less, or 1.8 nm or less, or 1.6 nm or less.
8. The PD of the porous carbon skeleton 90 8. A particulate material according to any one of claims 1 to 7, wherein the pore size is 10nm or less, or 8nm or less, or 6nm or less, or 5nm or less, or 4nm or less, or 3nm or less, or 2.5nm or less, or 2nm or less.
9. The PD of the porous carbon skeleton 95 A particulate material according to any one of the preceding claims, wherein the pore size is 15 nm or less, or 12 nm or less, or 10 nm or less.
10. A particulate material according to any one of claims 1 to 9, wherein the porous carbon skeleton has a unimodal pore size distribution.
11. 10. The method of claim 1, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution. The particulate material according to any one of claims 1 to 4.
12. 12. The particulate material of claim 11, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 2.5 nm to 20 nm.
13. 13. The particulate material of claim 12, wherein the porous carbon skeleton has a bimodal or multimodal pore size distribution with at least one peak below 2 nm and at least one peak in the range of 2.5 nm to 15 nm.
14. The porous carbon skeleton has a diameter in the range of more than 50 nm to 100 nm and a total volume of P 2 cm 3 / g, where P 2 is 0.2 x P 1 or less than 0.1 x P 1 Less than or equal to 0.05 x P 1 or less than 0.02 x P 1 or less than 0.01 x P 1 Less than or equal to 0.005 x P 1 A particulate material according to any one of claims 1 to 13, wherein:
15. 15. A particulate material according to any preceding claim, wherein at least some of the micropores and / or mesopores comprise voids completely surrounded by electroactive material.
16. The composite particles have a D of 9.5 μm or less, or 9 μm or less, or 8.5 μm or less, or 8 μm or less, or 7.5 μm or less, or 7 μm or less, or 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less. 90 A particulate material according to any one of claims 1 to 15, having a particle size.
17. The composite particles have a D in the range of 0.5 μm to 7 μm. 50 A particulate material according to any one of claims 1 to 16, having a particle size.
18. The composite particles have a D of at least 1 μm, or at least 1.5 μm, or at least 2 μm, or at least 2.5 μm, or at least 3 μm. 50 20. The particulate material of claim 17 having a particle size.
19. The composite particles have a D of 6.5 μm or less, or 6 μm or less, or 5.5 μm or less, or 5 μm or less, or 4.5 μm or less, or 4 μm or less, or 3.5 μm or less. 50 19. The particulate material of claim 17 or 18, having a particle size.
20. The composite particles have a D of at least 0.2 μm, or at least 0.5 μm, or at least 0.8 μm, or at least 1 μm, or at least 1.5 μm, or at least 2 μm. 10 A particulate material according to any one of claims 1 to 19 having a particle size.
21. The composite particles have a D of 25 μm or less, or 20 μm or less, or 18 μm or less, or 15 μm or less, or 12 μm or less, or 10 μm or less, or 9 μm or less, or 8 μm or less, or 7 μm or less, or 6 μm or less, or 5 μm or less. 99 A particulate material according to any one of claims 1 to 20, having a particle size.
22. 22. A particulate material according to any one of the preceding claims, wherein the volume-based particle size distribution is positively skewed.
23. The composite particles have an average molecular weight of at least 0.70, preferably at least 0.85, more preferably at least 0.90, more preferably at least 0.92, more preferably at least 0.93, more preferably at least 0.94, more preferably at least 0.
95. Sphericity S av The particulate material according to any one of claims 1 to 22, which is a spheroidal particle having the following structure:
24. A particulate material according to any one of the preceding claims, wherein the loading of the electroactive material in the porous carbon skeleton is up to 55%, preferably between about 25% and about 45%.
25. A particulate material according to any preceding claim, wherein the electroactive material is selected from silicon, tin, germanium and aluminium, and mixtures thereof.
26. The electroactive material is silicon and the weight ratio of silicon to carbon is [0.5×P 1 ~1.7 x P 1 26. The particulate material of claim 25, wherein the Mn content is in the range of 1:
1.
27. The electroactive material is silicon and the weight ratio of silicon to carbon is [0.5×P 1 ~1.3 x P 1 ]: range of 1, or [0.55 × P 1 ~1.1 x P 1 ]: range of 1, or [0.6 × P 1 ~1.1 x P 1 ]: range of 1, or [0.6 × P 1 ~1xP 1 ]: range of 1, or [0.6 × P 1 ~0.95 x P 1 ]: range of 1, or [0.6 × P 1 ~0.9 x P 1 ]: range of 1, or [0.65 × P 1 ~0.9 x P 1 ]: range of 1, or [0.65 × P 1 ~0.85 x P 1 ]: range of 1, or [0.65 × P 1 ~0.8 x P 1 ]: range of 1, or [0.7 x P 1 ~0.8 x P 1 27. The particulate material of claim 26, wherein the Mn content is in the range of 1:
1.
28. The electroactive material is silicon and the weight ratio of silicon to carbon is [1×P 1 ~1.7 x P 1 ]: range of 1, or [1.1 x P 1 ~1.7 x P 1 ]: range of 1, or [1.1 x P 1 ~1.65 x P 1 ]: range of 1, or [1.1 x P 1 ~1.6 x P 1 ]: range of 1, or [1.15 x P 1 ~1.6 x P 1 ]: range of 1, or [1.15 x P 1 ~1.55 x P 1 ]: range of 1, or [1.15 x P 1 ~1.5 x P 1 ]: range of 1, or [1.2 × P 1 ~1.5 x P 1 ]: range of 1, or [1.25 x P 1 ~1.5 x P 1 ]: range of 1, or [1.3 × P 1 ~1.5 x P 1 27. The particulate material of claim 26, wherein the Mn content is in the range of 1:
1.
29. 29. A particulate material according to any one of claims 25 to 28, wherein the electroactive material is silicon and at least 90% by weight, preferably at least 95% by weight, more preferably at least 98% by weight of the silicon mass in the composite particles is located in the interior pore volume of the porous carbon skeleton.
30. 30. A particulate material according to any one of claims 25 to 29, wherein the electroactive material is silicon and wherein, when the particulate material is analysed by TGA in air at a temperature ramp rate of 10°C / min, not more than 10% of the silicon content of the particulate material is unoxidised at 800°C, preferably not more than 5%, more preferably not more than 2%.
31. The volume of the micropores and mesopores of the composite particles measured by nitrogen gas adsorption is 0.15×P 1 or less than 0.10 x P 1 Less than or equal to 0.05 x P 1 or less than 0.02 x P 1 31. The particulate material according to any one of claims 1 to 30, wherein:
32. The composite particles are 150 mm 2 / g or less, or 100m 2 / g or less, or 80m 2 / g or less, or 60m 2 / g or less, or 40m 2 / g or less, or 30m 2 / g or less, or 25m 2 / g or less, or 20m 2 / g or less, or 15m 2 32. The particulate material of any one of the preceding claims, having a BET surface area of no more than 1 / g.
33. The composite particles are at least 0.1 m 2 / g, or at least 1 m 2 / g or less Both are 2m 2 / g, or at least 5m 2 33. The particulate material according to any one of the preceding claims, having a BET surface area of 1 / g.
34. 34. The particulate material of any one of claims 1 to 33, having a specific capacity when lithiated of from 1200 mAh / g to 2340 mAh / g.
35. A composition comprising a particulate material according to any one of the preceding claims and at least one other ingredient.
36. 36. The composition of claim 35, comprising at least 50% by weight, or at least 55% by weight, or at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight of the particulate material of any one of claims 1 to 34, based on the total dry weight of the composition.
37. 37. A composition according to claim 35 or 36, comprising the particulate material according to any one of claims 1 to 34 and at least one other component selected from: (i) a binder; (ii) a conductive additive; and (iii) an additional particulate electroactive material.
38. 40. The composition of claim 37 comprising at least one additional particulate electroactive material.
39. 40. The composition of claim 38, wherein the at least one additional particulate electroactive material is selected from graphite, hard carbon, silicon, tin, germanium, gallium, aluminum, and lead.
40. 40. The composition of any one of claims 37 to 39, optionally comprising a binder in an amount of from 0.5% to 20% by weight, or from 1% to 15% by weight, or from 2% to 10% by weight, based on the total dry weight of the composition.
41. 41. The composition of any one of claims 37 to 40, optionally comprising one or more conductive additives in a total amount of from 0.5 wt.% to 20 wt.%, or from 1 wt.% to 15 wt.%, or from 2 wt.% to 10 wt.%, based on the total dry weight of the composition.
42. 35. An electrode comprising a particulate material according to any one of claims 1 to 34 in electrical contact with a current collector.
43. 43. An electrode as claimed in claim 42, wherein the particulate material has the form of a composition as claimed in any one of claims 35 to 41.
44. (i) an anode comprising the electrode of claim 42 or 43; (ii) a cathode comprising a cathode active material capable of releasing and reabsorbing metal ions; (iii) an electrolyte between the anode and the cathode; A rechargeable metal ion battery comprising:
45. Use of a particulate material according to any one of claims 1 to 34 as an anode active material.
46. The use according to claim 45, wherein the particulate material has the form of a composition according to any one of claims 35 to 41.
Citation Information
Patent Citations
Composite and method for producing the same
JP2016132608A
Composite carbon materials comprising lithium alloying electrochemical modifiers
US20140272592A1
Carbon material for negative electrode of lithium secondary battery, negative electrode of lithium secondary battery, lithium secondary battery and method for producing carbon material for negative electrode of lithium secondary battery
WO2010038609A1
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
WO2017040299A1
Lithium secondary battery
JP2003100284A
Cited By
Porous carbon, negative electrode active material, and method for producing the same
JP7929988B1